2019
DOI: 10.32999/ksu2312-3206/2019-4-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Characteristics of Metacognitive Monitoring in Learning Activities of Students

Abstract: У статті автор проаналізував основні теоретичні підходи та методологічні методи щодо розуміння метакогнітивного моніторингу особистості. Мета статті-теоретично проаналізувати підходи до вивчення метакогнітивного моніторингу та його зв'язку з ефективною навчальною діяльністю студентів у ЗВО. Також розглянуто його зв'язок із навчальною діяльністю студентів на основі аналізу теоретичних досліджень вітчизняних і закордонних учених. Методи. У роботі використані теоретичні і порівняльні методи дослідження метакогніт… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…In the light of the results of our theoretical analysis and empirical research, with the help of statistical analysis, we confirmed the hypothesis that there is a positive connection between the metacognitive characteristics of the subject's activity, namely metacognitive involvement, activity, and knowledge, and formed reflexive problem-solving strategies; that is, the more metacognitive characteristics the subject has developed, the more effective it is to use reflexive strategies to solve the problems. This result is consistent with some psychological studies about metacognitive involvement and monitoring (Avhustiuk, 2016;Balashov, 2019;Dotsevych, 2014;Flavell, 1979;Karpov, 2012;Nietfeld et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the light of the results of our theoretical analysis and empirical research, with the help of statistical analysis, we confirmed the hypothesis that there is a positive connection between the metacognitive characteristics of the subject's activity, namely metacognitive involvement, activity, and knowledge, and formed reflexive problem-solving strategies; that is, the more metacognitive characteristics the subject has developed, the more effective it is to use reflexive strategies to solve the problems. This result is consistent with some psychological studies about metacognitive involvement and monitoring (Avhustiuk, 2016;Balashov, 2019;Dotsevych, 2014;Flavell, 1979;Karpov, 2012;Nietfeld et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…The concepts mentioned above are considered mainly as a professional quality of personality in the context of pedagogy, educational psychology, general psychology and cognitive psychology. In particular, the reflexive processes have been studied by such as the following national psychologists Balashov, 2019;Dotsevych, 2014;Balashov et al, 2018;Maksymenko, 2017;Pasichnyk et al, 2014;Savchenko, 2016;Tytarenko, 2013. Self-reflection and metacognition at the personal level is considered in the studies of Dunlosky and Metcalfe, 2009;Hrynkiv, 2016;Karpov, 2012;Kholodnaya, 2002;Koriat and Bjork, 2005.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation